Identification and Detailed Characterization of Metal Oxide Powders as a Fundamental Chemical Product - Ohtani, Bunsho; Nitta, Akio; Takase, Mai; Takashima, Mai (KnE Social Sciences, 2019)
Here we propose a method for identification and detailed characterization of metal-oxide powders with patterns of energy-resolved density of electron traps (ERDT) and conduction-band bottom (CBB) position, as a fingerprint, measured by newly developed reversed double-beam photoacoustic spectroscopy (RDB-PAS). Keywords: Electron Traps, Photoacoustic Spectroscopy, Metal-oxide Powders, Degree of Coincidence